Public awareness on electromagnetic field in Malaysia - Tukimin, R.; Wan Mahadi, W.N.L.; M Ali, M.Y.; M Thari, M.N. (2009)
Electromagnetic field (EMF) can be categorized as non-ionizing radiation (NIR) and known to be hazardous since it has ability to induce health effects to the exposed person if amount received is excessive. The wide spread of EMF relevant technologies related to microwave, radio frequency, extremely low frequency electromagnetic field (ELF EMF) contributed more electromagnetic fields to the environment and bringing out worry to the public as it has been related to the health issue. The misunderstanding on EMF facts has spread out by the public and has created big issue due to the wrong information and facts. We have conducted several safety assessment and talk on EMF awareness among the public. The objective of the safety talk was to make the public understand of basic knowledge on NIR and to advise them on the outcomes of the assessment base on recommendation of the standard guidelines issued by the International Committee on Non-ionising Radiation Protection (ICNIRP). We emphasized on EMF basics, effects, safety guidelines and exposure limits for workers and public to make the public understanding on EMF radiation better. In this paper, we also will highlight the results of safety assessment conducted at two locations which exposed to the ELF EMF.